1973
DOI: 10.1111/j.1476-5381.1973.tb08379.x
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the learning deficit following hyoscine administration to man

Abstract: Summary1. Twelve volunteer subjects completed a free-recall word learning test, a number-colour association test, and a scanning task after the following treatments: saline 1 ml, hyoscine 04 mg, or atropine 0-6 mg, administered by intravenous injection.2. Performance on all three tests was not significantly impaired after atropine. 3. Performance on the two learning tests but not on the scanning task, was significantly impaired after hyoscine. 4. Analysis of the results of the free-recall word learning test in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
67
0
3

Year Published

1977
1977
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(72 citation statements)
references
References 13 publications
2
67
0
3
Order By: Relevance
“…This may be one factor that has contributed to the apparently inconsistent findings between studies that have and those that have not used active placebos in their control groups when studying the effects of scopolamine on attention, working memory, and item and associative memory (Beatty et al, 1986;Caine et al 1981;Crow & Grove-White, 1973;Ghoneim & Mewaldt, 1977;Grober et al, 1989;Mintzer & Griffiths, 2001Robbins et al, 1997;Safer & Allen, 1971;Sherman et al, 2003). Scopolamine injection has been found to significantly impair paired-associate memory for free recall of number-color associations (Crow & Grove-White, 1973), and cued recall of name in face-name associations (Sperling et al, 2002), but not for cued recall of digit in symbol-digit associations (Beatty et al, 1986), cued recall of self-generated (i.e., generated by free association with a given cue) and well-rehearsed semantic and phonemic word paired associates (Caine et al, 1981), or cued recall of colored pattern in colored pattern-spatial location associations (Robbins, et al, 1997). However, it is important to note that both Beatty et al (1986) and Caine et al (1981) combined active placebo (glycopyrrolate or methylscopolamine) and inactive placebo (saline) groups to obtain their control groups used for comparison to their scopolamine groups.…”
Section: Relation To Memory Pathology In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be one factor that has contributed to the apparently inconsistent findings between studies that have and those that have not used active placebos in their control groups when studying the effects of scopolamine on attention, working memory, and item and associative memory (Beatty et al, 1986;Caine et al 1981;Crow & Grove-White, 1973;Ghoneim & Mewaldt, 1977;Grober et al, 1989;Mintzer & Griffiths, 2001Robbins et al, 1997;Safer & Allen, 1971;Sherman et al, 2003). Scopolamine injection has been found to significantly impair paired-associate memory for free recall of number-color associations (Crow & Grove-White, 1973), and cued recall of name in face-name associations (Sperling et al, 2002), but not for cued recall of digit in symbol-digit associations (Beatty et al, 1986), cued recall of self-generated (i.e., generated by free association with a given cue) and well-rehearsed semantic and phonemic word paired associates (Caine et al, 1981), or cued recall of colored pattern in colored pattern-spatial location associations (Robbins, et al, 1997). However, it is important to note that both Beatty et al (1986) and Caine et al (1981) combined active placebo (glycopyrrolate or methylscopolamine) and inactive placebo (saline) groups to obtain their control groups used for comparison to their scopolamine groups.…”
Section: Relation To Memory Pathology In Humansmentioning
confidence: 99%
“…In addition, short-term memory phenomena such as the recency component of a serial position curve (Crow & Grove-White, 1973;Frith et al, 1984) and digit span (Beatty et al, 1986;Drachman, 1978) are also spared. Recently, studies have shown that scopolamine may impact recognition memory processes by affecting both recollection and familiarity (Mintzer & Griffiths, 2001Sherman, Atri, Hasselmo, Stern, & Howard, 2003).…”
mentioning
confidence: 99%
“…Only a few studies have addressed the effects of scopolamine on paired associates. Scopolamine impaired encoding of paired associates in section VI of the Wechsler memory scale [29] encoding of number-color associations [22], and memory for self-generated paired associates [30]. A recent study using very strong pre-existing category associations showed no impairment [31].…”
Section: Reasons For Modeling the Effects Of Scopolaminementioning
confidence: 99%
“…Using muscarinic receptor antagonists (scopolamine or atropine), pervasive impairments of learning have been demonstrated in humans (Crow and Grove-White 1973), monkeys (Aigner et al 1991), rabbits (Harvey et al 1983, and rodents (Levin et al 1990). In many behavioral paradigms, the deficits produced by muscarinic-cholinergic antagonism are similar to the effects produced by hippocampal lesions (Watts et al 1981;Anagnostaras et al 1995), while in others they are more general (Hagan et al 1986;Rudy 1996;Paylor and Rudy 1990).…”
mentioning
confidence: 99%